PELAKSANAAN TRADISI BERSIH DESA GEMPOL SEBAGAI SIMBOL KOMUNIKASI BUDAYA - Shaliendri Alviana; Qoni’ah Nur Wijayani (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This research is entitled implementing the clean tradition of Gempol village as a symbol of cultural communication. This research aims to express gratitude to Allah SWT for the blessings given to the community in reaping abundant harvests, respecting the ancestors who cleared the village as a place to live and exist, implementing clean village traditions can strengthen solidarity between communities, preserving original regional culture. In this research the author wants to describe how signs and symbols communicate values, beliefs and cultural history in society. The method used in this research is descriptive qualitative research using the constructivism paradigm. The subject in the title of this research is